ANALISIS BEBAN KERJA FISIK OPERATOR PANEN KELAPA SAWIT MENGGUNAKAN METODE BIOMEKANIKA - Khairunnisa Khairunnisa; Meri Andriani; Wiky Sabardi (Fakultas Teknik Universitas Muhammadiyah Jakarta, 2023)
Palm Oil Mill PT. Perkebunan Nusantara I (PKS PTPN 1) Tanjung Seumentoh is a company that processes palm oil into Crude Palm Oil (CPO) with a production capacity of 45 tons of Fresh Fruit Bunches (FFB)/hour with a factory area of Â±10 Ha. Harvesting of oil palm fruit is done manually using the Egrek tool. The purpose of this study was to identify the compressive force and lift index of oil palm harvesting operators. The research stages, there are three stages of research, namely the first stage, namely the survey of the research location, the second stage of collecting research data on the number of workers, age of workers, weight of equipment, and height of equipment used to harvest oil palm fruit, the third stage is data processing using the Biomechanics method with calculations the maximum. Permissible Limit (MPL) Recommended Weight Limit (RWL). The method used, Biomechanics is divided into two methods, namely Maximum Permissible Limit (MPL) and Recommended Weight Limit (RWL). Results and discussion, from the calculation of RWL on 8 operators obtained an average Horizontal Multiplier (HM) 0.89, Vertical Multiplier (VM) 62,41625, Distance Multiplier (DM) 1.01875, Asymmetric Multiplier (AM) 1. MPL calculation from 8 operators obtained an average average Wtotal 421.79, Abdominal Pressure (PA) 1.8, Muscle force 681.79, Wrist Moment 1.05, Sacral Moment 11.47375, Total Moment 35.06. In conclusion, the compressive force on 8 oil palm harvesting operators with an average Recommended Weight Limit (RWL) of 1173.3 N and an average value of Maximum Permissible Limit (MPL) of 715.8 N. Workload on 8 operators with an average value -average 0. The method used, Biomechanics is divided into two methods, namely Maximum Permissible Limit (MPL) and Recommended Weight Limit (RWL). Results and discussion, from the calculation of RWL on 8 operators obtained an average Horizontal Multiplier (HM) 0.89, Vertical Multiplier (VM) 62,41625, Distance Multiplier (DM) 1.01875, Asymmetric Multiplier (AM) 1. MPL calculation from 8 operators obtained an average average Wtotal 421.79, Abdominal Pressure (PA) 1.8, Muscle force 681.79, Wrist Moment 1.05, Sacral Moment 11.47375, Total Moment 35.06. In conclusion, the compressive force on 8 oil palm harvesting operators with an average Recommended Weight Limit (RWL) of 1173.3 N and an average value of Maximum Permissible Limit (MPL) of 715.8 N. Workload on 8 operators with an average value -average 0. The method used, Biomechanics is divided into two methods, namely Maximum Permissible Limit (MPL) and Recommended Weight Limit (RWL). Results and discussion, from the calculation of RWL on 8 operators obtained an average.